Evaluation of Key Factors of Logistics Risks for Overseas EPC Projects - Jingshi He; Dai Han (Advances in Civil Engineering)
Correctly identifying and evaluating the logistics risks of EPC (engineering procurement construction) projects is conducive to strengthening the risk prevention and control of engineering projects. An evaluation index system for the logistics risk factors of overseas EPC projects was established, and the entropy-DEA (Data Envelopment Analysis) method used to evaluate and sort risk decision-making unit (DMU) with risk likelihood and risk consequences as decision variables. The risk reduction ratio and improvement space of each risk DMU are obtained, and the risk factor distribution matrix is constructed, pointing out that legal risks, operational risks and management risks are the primary risk DMU, which provide reference decisions for the optimal allocation of resources. Finally, it is proposed to carefully select overseas logistics carriers, conduct in-depth research before formulating logistics plans, pay attention to logistics process tracking and supervision, and strengthen logistics packaging and bundling technologies.